Web-Based Counseling Problem-Solving Model for Improving Mental Health in Students During the Covid-19 Pandemic - Siti Khadijah; Widodo Widodo; Endang Sulistyowati (IJNP (Indonesian Journal of Nursing Practices), 2023)
Background: There was an increase of mental health problems during the Covid-19 Outbreak caused by fears of contracting COVID-19, Increasing mental health problems in college students due to the Covid-19 outbreak caused by fears of contracting COVID-19, difficulty understanding online learning materials, decreased academic achievement, limited activities, finances, and boredom during the stay at home. Objective: To analyze a web-based problem-solving counseling model to improve mental health in students during the Covid-19 pandemic.Method: Quasi-experimental design using a pre-post test with a control group. The population was all first-year students at Surakarta College of Health, who were sampled with a purposive sampling technique. Inclusion criteria:  students who were experiencing anxiety, stress, depression, and suicide risk. There were a total of 60 respondents in the control group and 60 respondents in the intervention group. Data was collected using thequestionnaires Suicide Behavior Questioner-Revisi (SBQ-R) and Depression Anxiety Stress Scales (DASS). The web application intervention consisted of up-to-date testimonials, questionnaires, inspirational videos, and counseling options. The tests used were the dependent test and the independent test.Result: There was a significant improvement of participant mental health with and results found a reduction to the the risk of suicide, depression, stress, and anxiety.Conclusion: The Web-Based Problem-Solving Counseling Model is  effective in improving students' mental health during the COVID-19 pandemic( p0.05), and can be used as an alternative strategyfor students to address  their mental health problems while maintaining privacy and low levels of stigma.